The Effectiveness of a Communicative Imla’ Textbook in Improving Short Course Student’ Arabic Spelling Skills - Zaid, Abdul Hafidz bin; Mahmudi, Ihwan; Hizbullah, Nur; Ashari, Maulana; Anhar, Anhar (Universitas Islam Negeri Raden Intan Lampung, 2023)
Arabic Camp is a short Arabic language course program held by the Center for Education and Training (pusdiklat), University of Darussalam Gontor. This program was carried out to enhance students' speaking skills. However, the program seemed to face obstacles when dealing with students’ spelling skills (imla'). Most students can speak good Arabic but struggle to write basic Arabic words according to its rules. Early studies suggested that the Center has yet to have well-established teaching material for Imla’. Hence, this article aimed to design and find its effectiveness in improving students' spelling skills. Research & Development (R&D) methodology and used five instruments were used to collect data such as observation, interviews, questionnaires, tests, and documents. In analyzing data, Paired Sample t-Test is used. The procedures started with the literature review, planning, designing, validating, and experiment. The results of this research were the teaching materials in the form of a textbook. This study also suggested that the textbook validity is in good grade with a percentage score of 84.65%, meaning that the designed materials can be used with some modification and correction. As for its effectiveness, the Sig. (2-tailed) result is (0,000) < (less than) (0,005). It means that the textbook effectively improves students' spelling skills. In conclusion, the current study underscores a collective push towards innovative teaching materials in enhancing language education.